Enhancing refractive index sensing capability with hybrid plasmonic–photonic absorbers. Issue 17 (7th May 2015) - Liu, Zhengqi; Yu, Meidong; Huang, Shan; Liu, Xiaoshan; Wang, Yan; Liu, Mulin; Pan, Pingping; Liu, Guiqiang
<x xml:space="preserve">Abstract</x> A significantly enhanced refractive index sensor with a maximum figure of merit (FOM*) value of about 1337 has been demonstrated based on a hybrid plasmonic–photonic absorber via utilizing substantial absorption contrast between a perfect absorber (∼99% at normal incidence) and a non-perfect absorber when there are changes in the surrounding.